Intramammary infection caused by Staphylococcus aureus increases IgA antibodies to iron-regulated surface determinant-A, -B, and -H in bovine milk - Nagasawa, Yuya; Uchida, Ikuo; Tanabe, Fuyuko; Hirose, Aya; Sugawara, Kazue; Kiku, Yoshio; Iwata, Takehito; Kato, Chieko; Yamashita, Yusuke; Hayashi, Tomohito (Veterinary immunology and immunopathology, 2021)
•IsdA and IsdB as virulence factors were identified by bacteriophage expression libraries of S. aureus with antibodies in bovine mastitis milk.•OD values of IsdA & IsdB IgA/IgG antibodies increased in milk from naturally occurring mastitis caused by S. aureus.•Milk from experimental intramammary infections by S. aureus have significantly higher IsdA & IsdB IgA/IgG antibodies than pre-infusion milk.•However, IgG levels against IsdH in milk from S. aureus infections is not significant change. The aim of this study was to identify virulence factors that have high immunogenicity. An in vivo-expressed Staphylococcus aureus antigen was identified by probing bacteriophage expression libraries of S. aureus with antibodies in bovine mastitis milk. Eighteen clones were isolated, and their proteins were identified as 5 characterised proteins (IsdA, Protein A, IsdB, autolysin, and imidazole glycerol phosphate dehydratase) and 13 hypothetical proteins. We focused on IsdA, IsdB, and IsdH as virulence factors that have a high immunogenicity and are capable of inducing a specific humoral immune response in S. aureus-infected quarters. The optical density (OD) values of IsdA and IsdB IgA and IgG antibodies in milk affected by naturally occurring mastitis caused by S. aureus increased significantly compared to those in healthy milk. In the experimental infection study, the OD values of IsdA- and B-specific IgA and IgG antibodies were significantly increased from 2 to 4 weeks after S. aureus infection compared to day 0 (P < 0.05). On the other hand, we demonstrated that milk from natural and experimental intramammary infections caused by S. aureus are associated with significantly higher IgA levels against IsdH (P < 0.05), but no significant change in IgG levels. Our findings facilitated our understanding of the pathogenicity of S. aureus in bovine mastitis, as well as the mechanisms by which specific humoral immune responses to S. aureus infection are induced. In addition, the results obtained could provide insight into how bovine mastitis can be controlled, for example, through vaccination.